Local Technical Agroclimatic Committees are empowering 20,000 Guatemalan farmers to thrive despite climate change - Navarro Racines, Carlos; Castellanos, Andrea (2023)
The Local Technical Agroclimatic Committees (LTACs) approach was developed in 2015 to provide tailored climate information to farmers. Since 2017, it has been scaled out in Guatemala. In 2022, the LTACs were helping over 20,000 Guatemalan rural people to become more resilient in the face of climate change. Systematic co-design and improvement of Climate Information Services dissemination mechanisms with stakeholders has enabled co-producing and disseminating easy-to- understand local agroclimatic bulletins that are now effectively used by farmers to inform their decisions.